Gut microbiota changes and chronic hepatitis C virus infection. (2nd September 2017) - Preveden, Tomislav; Scarpellini, Emidio; Milić, Natasa; Luzza, Francesco; Abenavoli, Ludovico
ABSTRACT: Introduction : Hepatitis C virus (HCV) infection is a global health problem with 150 million infected people worldwide. Liver can be greatly affected by changes in gut microbiota due to increased intestinal permeability with passage of microbial antigens into the liver through the portal circulation. The concept of 'gut-liver' axis is important to understand the pathophysiology of several liver diseases. Several recent studies also revealed that an altered gut microbiota can be implicated in the pathogenesis of HCV-induced chronic liver disease (CHC). Areas covered : An overview of intestinal microflora composition, host reaction during CHC, and a description of relevant clinical trials on the use of probiotics in this field. Expert commentary : HCV patients gut microbiota composition is stable over liver disease stages. This is a unique example of gut disbiosis stability vs. NAFLD, HBV, HIV, and HCV co-infected patients. The impact of HCV infection on intestinal permeability allows gut disbiosis starting, maintenance and its proinflammatory effect until liver cirrhosis and HCC development. HCV eradication has unraveled the strong impact of gut microbiota unbalance on liver disease development with possible future implications for probiotics use to change the natural history of cirrhosis progression.